Pengaruh Implementasi Core Tax System terhadap Kepatuhan Wajib Pajak di Indonesia - Yosafath Laksana; Lorina Siregar Sudjiman (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2026)
In the current digital era, public services are increasingly being transformed through technology, including tax administration systems. One of the major innovations implemented by the Indonesian government is the Core Tax System, an integrated tax administration system designed to improve service efficiency, data integration, and taxpayer compliance monitoring. This study aims to analyze the effect of Core Tax System implementation on taxpayer compliance in Indonesia. The research adopts a quantitative approach using primary data collected through questionnaires distributed to taxpayers. The collected data were tested using validity and reliability tests and analyzed through descriptive statistics and significance testing to examine the relationship between the research variables. The results indicate that the implementation of the Core Tax System has a positive and significant effect on taxpayer compliance, both partially and simultaneously. These findings suggest that tax system digitalization can serve as an important instrument in improving taxpayer compliance in Indonesia.